The emergence of heterotrophy in an eco-evolutionary model: modelling trophic transitions in a resource-based framework with naturally-bounded trait distributions - Cropp, R; Norbury, J (Springer, 2019)
A plankton eco-evolutionary model with an alga that has the metabolic pathways to allow it to function as an autotroph or heterotroph is considered. Ecological constraints dictate that the traits that describe the feeding preferences and abilities of the alga naturally have bounded distributions. The trait distributions are then non-normal, and evolve with the population as it changes its trophic behaviour from an autotroph to a heterotroph. A key result of the simulations is that the populations remain in ecological stasis for many generations while the trait mean slowly adapts—only at the conclusion of this transition does herbivory emerge. After initially adapting to improve its competitive performance as an autotroph, the adapting population eventually emerges as a heterotroph having maximised its share of the resources at the expense of its prey, previously its competitor.